Black Love: On the Colours of Feelings in “Confiteor” by Antoni Szandlerowski - Ejzak, Bartosz (Czytanie Literatury. Łódzkie Studia Literaturoznawcze, 2019)
The imagination of Antoni Szandlerowski in his collection of letters to Helena Beatus (Confiteor), his beloved one, is dominated by black. The aim of this article is to show that this colour plays a major role in Confiteor therefore it is used be the author most of the times. When he writes about how pure and beautiful Helena Beatus is, he uses metaphors such as: black dove, black iris, dark cloud, dark corridor. It shows how pessimistic about the future and how guilty about the love he felt Antoni Szandlerowski was. The internal conflict was caused by the will to fulfil as a lover and the duty to continue priestly services. Antoni Szandlerowski is full of doubts. He misses Helena Beatus and feels that he cannot be happy without her. On the other hand, he knows that they cannot make their desire to live side by side real. Since the world is a place of pain and misery where the love cannot thrive due to social norms, lovers can bind together only after death. This way of thinking led Szandlerowski to many neurological disorders, caused nightmares and a painful impression that the whole world around fades away. Szandlerowski uses symbols such as a black dove and a black iris to describe his beloved one and to show the dichotomy of his perception. Therefore love is the source of all the pain and suffering for him.